(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Myocardial infarction in women represents a significant challenge in modern medicine, as it is characterized by both a high risk of development and specific clinical features. This article examines the main risk factors for myocardial infarction in women, including hormonal changes, hereditary predisposition, lifestyle factors, and the presence of comorbid conditions. Particular attention is paid to the impact of arterial hypertension, diabetes mellitus, obesity, smoking, and psychoemotional stress on the development of the disease. Analysis of these factors highlights the importance of early prevention and timely identification of myocardial infarction risk in women.